Comparison of Laser Iridotomy and Lensectomy Outcomes for Acute Primary Angle Closure - Kei Iijima; Kazutaka Kamiya; Yoshihiko Iida; Nobuyuki Shoji (Journal of Ophthalmology)
Purpose. To compare the clinical outcomes of the different treatments for acute primary angle closure (APAC). Methods. We retrospectively reviewed the clinical charts of 87 eyes of 87 patients undergoing treatment for APAC. We investigated the best spectacle-corrected visual acuity (BSCVA), intraocular pressure (IOP), corneal endothelial cell density (ECD), and secondary interventions after each treatment. Results. The pretreated IOP was 56.4 ± 9.0 mmHg. As the first treatment for APAC, all eyes underwent topical 2% pilocarpine and systemic mannitol administration. Subsequent laser iridotomy (LI) and lensectomy were necessary in 29 eyes (33%) and 35 eyes (40%), respectively. Bullous keratopathy developed in 1 eye (1%), and following glaucoma surgery was required in 7 eyes (8%). The BSCVA at the final follow-up was 0.16 ± 0.53 and 0.01 ± 0.20 logMAR (Mann–Whitney U test, p=0.149), the IOP was 12.8 ± 2.6, and 12.6 ± 2.9 mmHg (p=0.860), and the ECD was 2295.9 ± 658.2 and 2244.1 ± 622.0 cells/mm2 (p=0.735) in the LI and lensectomy groups, respectively. Conclusions. Approximately 26% of eyes with APAC were resolved after the initial medical treatment, and subsequent surgical treatments, such as LI and lensectomy, were required in 33% and 40% of eyes, respectively. We found no significant differences in the BSCVA, the IOP, or the ECD among LI and lensectomy treatment groups.